Factor Assocoated with Stigma Towards People Living With HIV/AID Among Nursing Students - Anselmus Aristo Parut; I Gusti Ayu Puja Astuti Dewi; Pw wulandari (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2019)
Background: Stigma towards people living with HIV/AIDS is a problem in control, prevention and treatment of HIV/AIDS. Stigma by health care worker in hospital is one of the main challenges in preventing and manage HIV/AIDS especially in developing country. Methods : this is a cross-sectional study, respondents were bachelor of nursing students program regular, program transfer and recognition of prior learning program. We used KQ-18 questionnaire to assess HIV/AIDS related knowledge, belief and values questionnaire to asses religiosity, modified Nurse AIDS Attitude Scale to assess stigma and stigma perception in workplace. Data were analyzed using SPSS 20. Descriptive statistics were conducted to summarize the sample characteristics. Results: A total 132 nursing students participated, recognition of prior learning nursing students have higher knowledge about HIV/AIDS (mean=13,84), bachelor of nursing students regular program have higher stigma (mean=96,30), person correlation analysis showed that there is a significant correlations between knowledge and stigma towards people living with HIV ( p= 0,001), regression analysis showed that p value = 0,000 which mean that educational background, work experiences and knowledge simultaneously affect stigma towards people living with HIV/AIDS. Conclusions : the finding of this research showed high magnitude of stigma towards people living with HIV/AIDS among nursing students, training and continuing education are needed to improve knowledge and reduce stigma towards people living with HIV/AIDS.